Mechanical properties of fly ash alkaline-based mortars containing recycled aggregates and reinforced by hemp fibres summited to accelerated carbonation - Mastali, Mohammad (2019)
Natural fibres are a sustainable and renewable resource available almost all over the world. Being cost effective and as stronger as synthetic fibres they are of interested for the production of reinforced cementitious composites for the construction industry. That is why research on cement composites reinforced by natural fibres constitute an important trend on the sustainability context. Still some its components like hemicellulose and lignin can hinder cement hydration. Natural fibres can degrade in high alkaline environment of Portland cement composites but several authors showed that carbonation is associated to a lower alkalinity that can help preserve both the properties and durability of composites reinforced with natural fibres. This means that accelerated carbonation of composites reinforced with natural fibres has not only carbon sequestration advantages but is also especially indicated for such composites. This paper discloses results of an investigation concerning the performance of fly ash/waste glass alkaline-based mortars with recycled aggregates reinforced by hemp fibres submitted to accelerated carbonation